Analisis Kepuasan Aplikasi Anjungan Pasien AWS Berbasis Website Menggunakan Metode WEBQUAL 4.0 - Usman Usman; Joy Nashar Utama Jaya; Aditya Pratama (STMIK Budi Darma, 2022)
The use of the Website-based AWS Patient Pavilion application that has been implemented by Abdul Wahab Syahrani Hospital in providing services is one example or form of information technology advancement. To find out the quality of a Website-based application that has been implemented by the hospital, it is necessary to take measurements. By measuring the quality of the AWS Patient Pavilion Website, it is possible to know the level of satisfaction based on the perception of the end user.In this research, the researcher uses the WebQual method which has been modified by adding user satisfaction variables with three main dimensions of WebQual 4.0, namely Usability, Information, Service Interaction. This research was conducted at Abdul Wahab Syahrani Hospital. Data was collected by using questionnaires. The population of this study were patients who were in a halfway house as users of the AWS Patient Pavilion Website. The results of this research are suggestions for website development